Stable isotope evidence for diet change in Roman and Medieval Italy: local, regional and continental perspectives - Nitsch, EK (2012)
This thesis investigated dietary change in Roman and Medieval Europe c. AD 1-1500 using stable isotope analysis of humans and animals. Historical and archaeological data present two possibilities for how the social, political and economic changes of this period may have affected food practices. One argument suggests the population collapse and economic depression of the Early Medieval period increased the availability and consumption of meat. The counter- argument suggests that agricultural and economic patterns were constrained by local circumstances, and that no significant dietary change occurred. This study combined local-scale isotopic analysis from central Italy with a meta-analysis of all available previously published data from Europe c. AD 1-1500. Mixed multi-level models were used to control for random inter-site variation, and to investigate the effect of multiple factors (Phase, Location, proximity to coast, Age, Sex, Species) on d13C and d15N. Within central Italy, 430 humans and 29 animals were analysed from eight archaeological sites dating from the 5th century BC to the 15th century AD. There were no significant differences through time, but coastal sites had significantly higher d13C and urban sites had significantly higher d15N. Across Europe, Early Medieval humans (c. AD 500-1000) had slightly but significantly lower d13C and d15N compared to Roman and Late Medieval individuals. This was the opposite of the effect expected due to increasing meat consumption at this time. A number of complicating factors were discussed, including the effect of climate change, changing agricultural practices and uncertainty in estimating animal protein consumption based on d13C and d15N. When these effects are considered, the isotopic changes observed through time do not eliminate the possibility of increased meat consumption in the Early Medieval period. Nevertheless, the data presented from Roman Italy, and new models for estimating animal protein consumption, indicate that Roman historical sources may underestimate the dietary role of animal protein, and that therefore Roman and Early Medieval food production and consumption patterns were similar.